Partial-density of occupied valence states by x-ray standing waves and high-resolution photoelectron spectroscopy - J. C. Woicik (Superficies y vacío, 2000)
We describe an experimental method by which site-specific valence-electronic structure may be obtained. Itutilizes the spatial dependence of the electric-field intensity that results from the superposition of the incidentand reflected x-ray beams within the vicinity of a crystal x-ray Bragg reflection. Resolution of the anion andcation contributions to the GaAs valence-band density of states is demonstrated